The U-boat hunters : the Royal Canadian Navy and the offensive against Germany's submarines - Milner, Marc (Heritage., 1994)
The U-Boat Hunters, which completes Milner's analysis of the RCN's battle with Germany's submarines, is a pioneering study of the final years of the Atlantic war and a landmark work in both Canadian and modern naval history.